Strategi Usaha Mikro Kecil dan Menengah (UMKM) dalam Digitalisasi Pemasaran untuk Kesejahteraan Masyarakat - Helmita Helmita; Yudhinanto CN (IPM2KPE, 2023)
This study aims to determine the MSME strategy, determine the factors in marketing digitalization and find out the obstacles faced by MSME actors when carrying out digital marketing systems for the welfare of society. This research is a qualitative descriptive research. The research subjects are MSME actors, the community as users and the general public as consumers. Data collection techniques using interviews, observation and literature study. Data analysis techniques using qualitative descriptive analysis. The results of the study show that the strategy for small and medium enterprises in digitizing marketing really needs the right strategy in order to improve the welfare of the community both as MSME actors and as workers in MSME locations. apart from being the owner of MSME actors, they also play an important role in designing strategies in marketing digitalization so that they continue to survive amid the economic downturn due to the impact of the pandemic that hit. Keywords: Marketing Digitalization, Community Welfare, MSME Strategy